Soil chemical characteristics, biomass production and levels of nutrient and heavy metals in corn plants according to doses of steel slag and limestone - CAETANO, LUIZ CARLOS SANTOS (Revista Ceres, 2017)
Steel slag presents potential for neutralizing the soil acidity instead of limestone and for supplying nutrients for plants. The objective of this work was to study the effect of steel slag on soil chemical characteristics, biomass production, and contents of nutrients and of heavy metals on dry matter of corn plants. The levels of P, K, Na, Ca, Mg, Cu, Fe, Zn, Mn, Si, Cd, Cr, Pb, and Ni were determined in steel slag and limestone (for comparison purposes) and the growth of corn plants under increasing doses of slag and limestone (0 to 10 t ha-1) was evaluated. Steel slag presented higher levels of P, Fe, Zn, Mn, and Si when compared with limestone. No difference was found in the content of heavy metals of slag and limestone, except for Cr, which was higher in the slag. Limestone provided the greatest increase of soil pH over time. Slag increased the content of P, Si, and soil micronutrient, while limestone was more efficient in increasing the content of Mg. The levels of heavy metals in the soil increased with the application of slag, but they remained below critical level within agricultural parameters. Slag and limestone presented a similar effect on the increase of the initial production of corn biomass. The levels of heavy metals in dry matter of corn plants under increasing doses of slag and limestone were below the critical levels of the toxicity of these elements on most plants.